A review of cosmetic and personal care products: halal perspective and detection of ingredient - Hashim, Puziah; Mat Hashim, Dzulkifly (Universiti Putra Malaysia Press, 2013)
The term halal refers to what ispermitted by Islamic law. It is a basic need for Muslims and encompasses all materials used in everyday life including cosmetics.Muslims want to be assured that the ingredients,handling, processing, distribution, transportation and types of cosmetic used are halal compliant. The halalaspects of cosmetic and personal care products cover ingredients, all the processes involved in production right up to delivery to consumers, safety and product efficacy evaluations. In order to verify halal compliance of cosmetic products, a method of detecting halal and non-halal ingredients is very important and critically needed. Halal cosmetic standards, halal certification and the halal logo can be used as benchmarks for halal compliance. In view of the importance of cosmetic and personal care products from the halal perspective, this review will cover the halal principles, halal cosmetic and personal care products, ingredients, standard and certification as well as safety. The development of the process of detecting non-halal ingredients and authenticating halal ingredients for potential cosmetic applications in recent years are included in this paper.